Harkhuf’s Autobiographical Inscriptions. A study in Old Kingdom Monumental Rhetoric: Part I. Texts, Genres, Forms - Stauder-Porchet, Julie (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
Harkhuf’s facade, inscribed with diverse types of texts, is a unitary composition. Inscriptional layout on that facade is highly complex and contributes directly to the rhetoric of the texts as inscriptions. The facade inscribes royal agency at the place, in the far south, that is farthest away from the Memphite center. Patterns of motion, out of the Valley and back to the Residence, are emphasized spatially on the wall. Along with an episodic narrative mode in the event autobiography, inscribed royal speech set Harkhuf and his monument as examples for posterity. As other facades subsequently inscribed at Qubbet el-Hawa demonstrate, this example was emulated indeed. Part I. Texts, genres, forms The architrave: offering formulae, ideal autobiography and other ritual texts Right and left sides of facade: expanded titulary and event autobiography The outer right of the facade: the royal letter Part II. The inscribed facade Verbal rhetoric: the facade as a unitary inscription Inscriptional layout on the facade The inscription as an event Harkhuf’s reception and emulation in inscribed facades at Qubbet al-Hawa